Note to the Spanish pharmacopoeia IX: calcium chloride edition - García Villanova, R.; Saenz de Buruaga y Lerena, J. (Ars Pharmaceutica (Internet), 1970)
A titrimetry and complexometric technics of evaluation of Calcium chloride has been revised. We recomanded a complexometric technic, using EDTA and murexide as indicator, in order to include both in the new Spanish Pharmacopeia edition.